A preliminary study on the oral acute toxicity of kintsay (Apium graviolens L.) in BFAD : ICR mice ICR mice - Aungon, Flordeliza S.; Gutierrez, Oscar G.
Kintsay (Apium graviolens L.) is know to have some diuretic and hypotensive effects in man. A preliminary study on the oral toxicity of kintsay in BFAD: ICR mice was carried out. A pure extract was prepared and orally administered to four groups of mice of each sex at the dose levels of 160, 240, 320 and 400 mg/kg body weight. The treatment resulted in one mortality for each sex from the highest dose group. The female died in 1 hour and 25 minutes post-treatment after showing signs of decrease motor activity, ataxia, head-shaking, lethargy and abdominal breathing, while the male died after 8 days without exhibiting any toxic signs and loss in body weight. Upon necropsy, the male mouse have enlarged liver and spleen. The estimated median lethal dose of kintsay in mice was more than 400 mg/kg body weight. The findings of the preliminary study in mice gave indication that kintsay at large single dose may have delayed systemic effects with deleterious consequence other than the immediate lethal toxic effect. A definitive oral acute toxicity test of kintsay is recommended in the future.(Author)
BFAD Laboratory Information Bulletin, 1995 1 (1) pages 5-8
Keywords: Apium; Toxicity Tests; Apium graviolens L; Kintsay